Decolonial feminism and contemporary art in the Americas - Martínez, Elisa de Souza; Martins, Isabela Capinzaiki Silveira (Farol, 2024)
We begin by investigating the production of female artists intersected in a sociological analysis of the arts in the Americas. The works of Rosana Paulino (1967 -) and Marcela Cantuária (1992 -) and their ways of representing issues of gender and decoloniality stand out. We analyze the plurality of pictorial constructions in the representation of gender violence and legacies of colonialism. This work identifies possibilities for sociological investigation of artistic production in the Americas, considering the specificities of different visual matrices.